2018
DOI: 10.1016/j.coal.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Insights into matrix compressibility of coals by mercury intrusion porosimetry and N2 adsorption

Abstract: Matrix compressibility and pore properties (pore size distribution) of a rank range of coals was investigated using mercury intrusion porosimetry (MIP) on coal cores with the pore size distribution also being determined using low temperature at 77 K nitrogen adsorption/desorption isotherms for crushed samples. The coal matrix compressibility is significant when the pressure of MIP is from 0.0074-35 MPa. Mathematical models were developed (based on MIP and nitrogen adsorption/desorption isotherms) to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
79
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 49 publications
8
79
1
Order By: Relevance
“…By using this method, Guo et al [23] calculated the coal matrix compressibility coefficients and found it emerges as a "U-shaped" trend with coal ranks. Cai et al [24] found the coal matrix compressibility coefficients are in the range of 0.24−13.56 × 10 −10 m 2 /N, and then they revealed the influence factors of compressibility in differently ranked coals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using this method, Guo et al [23] calculated the coal matrix compressibility coefficients and found it emerges as a "U-shaped" trend with coal ranks. Cai et al [24] found the coal matrix compressibility coefficients are in the range of 0.24−13.56 × 10 −10 m 2 /N, and then they revealed the influence factors of compressibility in differently ranked coals.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that it is a feasible method to evaluate coal matrix compressibility by combining low-temperature N 2 adsorption (LTNA) and MIP data [22][23][24]. By using this method, Guo et al [23] calculated the coal matrix compressibility coefficients and found it emerges as a "U-shaped" trend with coal ranks.…”
Section: Introductionmentioning
confidence: 99%
“…7 Because of the complex structure with a three-dimensional network, it is difficult for microorganisms to degrade and utilize coal. [8][9][10] Small molecular organics are dispersed in the polymer structure of coal. 11 Small and medium molecular organics in lignite and volatile bituminous coal account for approximately 10% to 23% of the total organic matter, and in some coal bodies, they even account for 30%.…”
Section: Introductionmentioning
confidence: 99%
“…The capillary pressure curve (CPC) experimentally obtained by mercury intrusion (also known as the mercury intrusion capillary pressure) has been found to be among the most effective data for studying the pore structure at a relatively large scale compared with the micron‐sized scanning electron microscopy images. The heterogeneity and anisotropy of pore structures are involved in the CPC; thus, the CPC has been applied to a wide range of natural or synthetic porous media, such as shale, tight sandstone, carbonate rock, packing bed, coal rock, cement slurry, and fine sediment containing natural gas hydrate (Cai et al, ; Lei & Santamarina, ; Sang et al, ; Voigt et al, ; Wyrzykowski et al, ). From the equivalent hydraulic size distribution of the pore‐throat (SDPT) given by the CPC, many critical pore structure parameters, such as the threshold pressure and radius, the maximum displacement pressure P d and its corresponding maximum pore‐throat radius r max , the average pore‐throat radius r mean , the irreducible water saturation S wir , the structural coefficient T , and the pore‐throat radius at any saturation (e.g., r 15 , r 25 , r 50 ), can be directly determined (Nooruddin et al, ).…”
Section: Introductionmentioning
confidence: 99%